Methodological approach for assessing relationships in company networks: an application example at a brazilian auto parts industry - Fusco, Prof. Dr. José Paulo Alves; Dias, Profa. MSc. Rosemeire do Carmo Mota (Revista Gestão da Produção Operações e Sistemas, 2012)
Many researchers emphasize the increasing dynamics of business globalization, virtually as a new order of driving rules to be considered and included regarding operations management. In this sense, and trying to attain a set of suitable competitive conditions according to the needs of their business, the very internal processes of management and decision making have been growing in terms of complexity and range of issues to be considered. To do so, it is important to understand and absorb possible changes in competitive conditions as they arise. This paper aims to present a conceptual model and a case study to illustrate the assessment of the relationships involving actors within an operations network. The understanding of the basis behind these relationships and the identification of the existing hierarchic profile governing them, represent primary items to be considered embedded in a decision making system. The results obtained suggest the possibility to make use of the proposed model as an auxiliary tool to assess existing relationships within an operations network. Keywords: Network; supply chain; decision making; concurrent networks.